2021
DOI: 10.1002/cncr.33495
|View full text |Cite
|
Sign up to set email alerts
|

National early access programs and clinical trials: What opportunities for early access to therapeutic innovations for patients with malignant melanoma?

Abstract: Tailoring clinical trial methods and design according to drug class and gathering systematically long‐term real‐life clinical data from national early access programs might be options to improve the reliability of drug development in metastatic melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Reimbursement is complicated by uncertainties across different treatments in upcoming new techniques and biomarkers. A temporary use authorisation system provides access to innovative drugs, allowing access for patients with cancer who have no therapeutic option to off-label and as-yet-unavailable drugs [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reimbursement is complicated by uncertainties across different treatments in upcoming new techniques and biomarkers. A temporary use authorisation system provides access to innovative drugs, allowing access for patients with cancer who have no therapeutic option to off-label and as-yet-unavailable drugs [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Novel therapeutic approaches now appearing are improving patients’ overall survival and quality of life and making early access to treatment—and accurate targeting—all the more important [ 104 , 107 ]. An international survey across 30 European countries concluded that 27% of 19,600 patients with advanced MM did not get access to the standard first-line therapy, often because of long delays between marketing authorisation and drug reimbursement [ 22 , 108 ]. Guidelines from European medical organisations promote the integration of care between medical and paramedical specialities and better management of MM from primary melanoma diagnosis through advanced disease palliation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the European Union (EU) there are two ways to marketing authorization (MA) of new drugs: a centralized process through the European Medicines Agency (EMA) and a national procedure (managed by national drug agencies) [ 1 – 4 ]. While MA is a precondition, it is not the only causal factor of market access in Europe [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…While MA is a precondition, it is not the only causal factor of market access in Europe [ 3 ]. Pricing and reimbursement (P&R) negotiation, which occurs at the national level, represents the second step of the access process [ 4 ]. P&R is complex to manage due to large variability in procedures, timelines, and criteria in each country’s P&R decision-making process [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%